Hybrid CsPbBr3 quantum dots decorated two dimensional MoO3 nanosheets photodetectors with enhanced performance - Dong Jin Lee; Ganesan Mohan Kumar; Youjoong Kim; Woochul Yang; Deuk Young Kim; Tae Won Kang; Pugazhendi Ilanchezhiyan (Journal of Materials Research and Technology, 2022)
Molybdenum trioxide (MoO3) have gained considerable attention for their wide applications ranging from optoelectronics, solar cells to energy storage. Herein, we obtained high crystalline MoO3 nanosheets (NSs) through a vapor phase epitaxy (VPE) method. A photodetector (PDs) based on MoO3 NSs was fabricated on the SiO2/Si substrate and the PDs exhibit a striking photoresponse under ultraviolet (UV) light. Furthermore, by introducing a CsPbBr3 QDs the photocurrent of the MoO3 devices was enhanced by 2 orders of magnitude than the pristine counterpart. The enhanced photocurrent could be ascribed to the interfacial charge transfer from CsPbBr3 QDs to MoO3. The hybrid CsPbBr3 QDs/MoO3 photodetectors exhibit high responsivity with high on/off ratio under UV light illumination. Furthermore, the performance of the hybrid device, extending from UV to visible light, has ensured broad spectral response of the device. This work indicates that CsPbBr3 QDs/MoO3 hybrids can be promising for the construction of broad band photodetectors and other optoelectronic devices.